The preliminary insight of internal-external NPD practices integration and product development time in geographically distributed environment - Ibrahim, Amlus; Dadriyansyah, G.; Ramayah, T. (2010)
Global competitiveness is one of the most important issues in manufacturing industry nowadays. Almost every company in this business industry is affected by it and they are looking for new ways to remain aligned and competitive. In recent years, the long term success of some manufacturing firms and organizations has been enhanced by their ability to bring new products onto the market at regular and shorter intervals. In order to achieve that, effective new product development requires a good integration and collaboration between internal and external participants. Moreover, in current circumstances, issues on how to effectively integrate NPD constituents in dispersed area are increasing. Therefore, this conceptual paper intends to explore ways in which internal and external new product development (NPD) practices might contribute to the acceleration of product development time in the context of geographically distributed environment. Concurrent engineering represents the internal NPD practices, while external NPD practices are reflected by supplier and customer involvement. Based on past literatures in the related field, some theoretical and practical implications of internal-external NPD practices integration in virtual environment are discussed.